2022
DOI: 10.1245/s10434-022-11462-y
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Impacts Prognosis of Patients Undergoing Resection for T1 Intrahepatic Cholangiocarcinoma

Abstract: Background. The prognostic impact of tumor necrosis among patients undergoing resection for intrahepatic cholangiocarcinoma (ICC) remains ill-defined. Methods. Patients who underwent curative-intent resection for ICC between 2000 and 2017 were identified using a multi-institutional database. The association of pathologic tumor necrosis with overall survival (OS) and recurrence-free survival (RFS) was examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Given the poor prognosis of CCA, especially iCCA, efforts have recently focused on improving prognostication and optimising selection criteria to identify the best candidates for surgery. 36 , 37 , 38 , 39 Traditional predictors of outcomes among patients with iCCA include tumour burden, differentiation, grade, microvascular invasion, lymph node metastasis and tumour markers (CA). 40 , 41 However, so far, available prognostic factors have not accurately predicted the prognoses of patients with iCCA.…”
Section: Discussionmentioning
confidence: 99%
“…Given the poor prognosis of CCA, especially iCCA, efforts have recently focused on improving prognostication and optimising selection criteria to identify the best candidates for surgery. 36 , 37 , 38 , 39 Traditional predictors of outcomes among patients with iCCA include tumour burden, differentiation, grade, microvascular invasion, lymph node metastasis and tumour markers (CA). 40 , 41 However, so far, available prognostic factors have not accurately predicted the prognoses of patients with iCCA.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there may be some risks of selection bias. Our study pulled worldwide population-based cohort studies with relatively large numbers of patients, 30,31 and these studies were assigned great weight. As a result, the pooled effect sizes tended to be consistent with the results of these population-based cohort studies.…”
Section: Publication Biasmentioning
confidence: 99%
“…After excluding 1818 duplicate studies, the titles and abstracts of the 4574 reports were scanned to exclude irrelevant research. In the end, 59 studies were pulled for full-text evaluation and 10 matching the inclusion criteria were finally included in the metaanalysis [23][24][25][26][27][28][29][30][31][32] (Figure 1). The characteristics and details of all included studies are shown in Table 1.…”
Section: Literature Research and Characteristics Of Studiesmentioning
confidence: 99%
“…Recent studies suggest that PNI may indicate a worse prognosis for ICC patients ( 10 - 12 ). Due to the varying prognoses within different subgroups of early ICC patients ( 13 , 14 ), despite the existing research on PNI in this population, the impact of PNI on the prognosis of early ICC patients still requires further exploration.…”
Section: Introductionmentioning
confidence: 99%